2014
DOI: 10.1080/09205063.2014.950033
|View full text |Cite
|
Sign up to set email alerts
|

Structural and permeability characterization of biosynthetic PVA hydrogels designed for cell-based therapy

Abstract: Incorporation of extracellular matrix (ECM) components to synthetic hydrogels has been shown to be the key for successful cell encapsulation devices, by providing a biofunctional microenvironment for the encapsulated cells. However, the influence of adding ECM components into synthetic hydrogels on the permeability as well as the physical and mechanical properties of the hydrogel has had little attention. Therefore, the aim of this study was to investigate the effect of incorporated ECM analogues on the permea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 78 publications
1
7
0
Order By: Relevance
“…Among these, photo‐polymerizable gelatin hydrogels are especially attractive as they offer the ability for spatial and temporal control over the polymerization process. Additionally, the reaction can be performed at room or physiological temperature, with fast curing rates and minimal heat generation …”
Section: Introductionmentioning
confidence: 99%
“…Among these, photo‐polymerizable gelatin hydrogels are especially attractive as they offer the ability for spatial and temporal control over the polymerization process. Additionally, the reaction can be performed at room or physiological temperature, with fast curing rates and minimal heat generation …”
Section: Introductionmentioning
confidence: 99%
“…However, these techniques require specialized biomaterials (bioinks), which generally have specific rheological properties that allow printing of constructs with high shape fidelity, as well as being cyto-compatible to support cell survival, function, and phenotype. Hydrogels, which are composed of highly hydrated polymeric networks, have shown great promise as bioinks due to their structural similarity to the native extracellular matrix. …”
Section: Introductionmentioning
confidence: 99%
“…In our preceding study, the controlled physico‐mechanical characteristics of the base PVA network was shown to be preserved after incorporation of a 1% of separate ECM molecules. More importantly, the heparin and gelatin did not interfere with the expected permeability of different FG/c PVA hydrogels, which is an essential feature determining the permselectivity capacity of these hydrogels for various biomedical applications including cell immunoisolation.…”
Section: Resultsmentioning
confidence: 91%
“…Solutions were then lyophilized to obtain dry macromers. A schematic representation of methacrylation reactions for PVA, heparin, and gelatin has been previously illustrated elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation